Evaluation of forage qualities of sorghum (Sorghum bicolor L.) under varying jeevamrit formulations and their spraying interval - MOHD. ARIF; RAVINDRA KUMAR; ARVIND KUMAR; D L GUPTA (Indian Journal of Animal Sciences, 2023)
An experiment was conducted at ICAR-Central Institute for Research on Goats, Makhdoom to generate precise information about different jeevamrit formulation and their spraying interval on forage quality of fodder sorghum during summer season of 2022. The treatments consisted of three jeevamrit formulations viz. jeevamrit-1 (5 kg cow dung + 2.5 litre cow urine), jeevamrit-2 (10 kg cow dung + 5 litre cow urine) and jeevamrit-3 (15 kg cow dung + 7.5 litre cow urine); and three spraying intervals viz. spraying at every one week’s interval, spraying at every two week’s interval and spraying at every three week’s interval. The experiment was laid out in factorial randomized block design with three replications. The results showed that among the different jeevamrit formulations, jeevamrit-3 and among the different spraying intervals, spraying at every one week’s interval recorded maximum total dry matter yield, crude protein, ether extract, TDN content, dry matter intake, relative feed quality, net energy for lactation, nitrogen, phosphorus and potassium content in forage sorghum. However, among the different jeevamrit formulations, jeevamrit-2 and jeevamrit-3; and among the different spraying intervals, spraying of jeevamirt at every one week and every two week’s interval recorded at par values of all the nutritive parameters in fodder sorghum.